Infrared is more effective in perineum wound healing during postpartum than iodine - Dewi, Vivian N. L.; Ayuningtyas, Ika F. (International Journal of Research in Medical Sciences, 2017)
Background: Maternal death during childbirth is usually caused by puerperal infection (11%) this happens because of a lack of care on the wound, bleeding (27%) (Due to the birth canal laceration and complications during parturition (8%). Many women feel too concerned about the perineum injury, so they afraid to do activities in the first days after delivering. It was necessary for the proper techniques in wound care, and the most important was the use of materials and the proper way, for example by using Far Infra-Red Therapy. The benefits of infrared light is able to activate the water molecules in the body, improve microcirculation, cleanse the blood, improve skin texture, so by utilizing far infrared, process of wound healing can take place more quickly. Methods: This study used Quasi-experiment with Pre-Post-test Control Group Design with Cross-sectional approach. Intervention group was using puerperal women given far infrared and control using puerperal women given iodine. The sampling technique was purposive sampling. Samples were puerperal women who suffered lacerations in perineum at RB Amanda. Samples were of 30 people that divided into two groups. Results: The results of independent t test p values are significant only on day 1 of 0.01, and Paired t test show a significant difference (p = 0.00) in the control group only at day 1 to 2 with a mean of 15. In the intervention group have a significant difference on day 1 to 2 (p = 0.00, mean = 31.7) and on day 2 and 3 (p = 0:04, mean = 5.7). Conclusions: Infrared therapy is more effective in perineum wound healing during postpartum.